Near-wall dynamics of concentrated hard-sphere suspensions: comparison of evanescent wave DLS experiments, virial approximation and simulations. Issue 37 (7th October 2015) - Liu, Yi; Bławzdziewicz, Jerzy; Cichocki, Bogdan; Dhont, Jan K. G.; Lisicki, Maciej; Wajnryb, Eligiusz; Young, Y.-N.; Lang, Peter R.
<x xml:space="preserve">Abstract</x> Comparing to EWDLS-experiments and simulation shows a virial approximation for colloidal near-wall dynamics to be valid up to intermediate densities.